A revised turtle assemblage from the Upper Cretaceous Menefee Formation (New Mexico, North America) with evolutionary and paleobiostratigraphic implications - Brent Adrian; Heather F. Smith; Andrew T. McDonald (PeerJ)
The middle Campanian Menefee Formation (Fm.) of the San Juan Basin of New Mexico is a relatively understudied terrestrial deposit in southern Laramidia preceding the fossil-rich upper Campanian Fruitland and Kirtland formations that have been studied for more than a century. Previous collection efforts have revealed a diverse dinosaurian and crocodyliform fauna in the Menefee Fm., including ankylosaurian, tyrannosaurid, hadrosaurid, ceratopsian, and neosuchian taxa. Nearly a decade has passed since the last description of the Menefee turtle fauna, and we present new material that provides insight into turtle evolution during the Campanian in the Colorado Plateau, with implications for Late Cretaceous turtle paleobiostratigraphy in Laramidia. In particular, we extend the stratigraphic ranges of the baenids Neurankylus baueri and Scabremys ornata backwards from younger San Juan Basin strata, along with the nanhsiungchelyid Basilemys. Additional material increases Menefee representation of the relict helochelydrid Naomichelys, and the regionally prevalent derived baenids Denazinemys and Thescelus. Additionally, we report new pan-trionychian specimens, which provide insight into the persistence of Adocus and multiple trionychid and plastomenid species through the remainder of the Campanian in the San Juan Basin. A cluster analysis of turtle diversity across early-middle Campanian sites in Laramidia shows distributions consistent with latitudinal provinciality in some groups. For instance, derived baenids were restricted to latitudes south of southern Utah, along with marine taxa (bothremydids and protostegids) and pan-kinosternoids. Basin-scale endemism is also suggested by some baenid and trionychid distributions. Otherwise, the turtle fauna of the Menefee most closely resemble those of the similarly-aged Wahweap Fm. in southern Utah, and the Aguja Fm. in the Big Bend area of Texas and Mexico to a lesser extent. The Menefee turtle assemblage is consistent with reconstructed paleoenvironments characteristic of the western shoreline of the Western Interior Seaway. Recurrent cyclothems in these settings shaped the development of fluviodeltaic deposits that preserved distal components of large channels with surrounding floodplains and swamps, along with evidence of freshwater, brackish, and possibly shallow marine influence.